2021
DOI: 10.5267/j.ijdns.2021.8.002
|View full text |Cite
|
Sign up to set email alerts
|

Integration of technology acceptance model and theory of reasoned action in pre-dicting e-wallet continuous usage intentions

Abstract: The purpose of this study is to determine the factors influencing continuous usage intention of E-Wallet in Denpasar City with integrating the Technology Acceptance Model (TAM) And Theory of Reasoned Action (TRA). This study applied a structural equation model analysis with 140 samples collected from E-Wallet users in Denpasar City. The results show that all three determinants of E-Wallet continuous usage intention, including perceived usefulness, perceived ease of use, and attitude. Recommendations are provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…This means that the higher the level of customers' perceived usefulness, the higher chance that repurchases intentions will occur. The result supported by Puspitasari & Briliana (2018); Dewi et al (2017); Dewi et al (2020); Rahmayanti et al (2021) The effect of perceived ease of use (X2) on repurchases intentions (Y) is 0.343; perceived ease of use has a positive and significant effects on repurchases intentions. This means that the higher the level of customers' perceived ease of use , the higher chance that repurchases intentions will occur.…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…This means that the higher the level of customers' perceived usefulness, the higher chance that repurchases intentions will occur. The result supported by Puspitasari & Briliana (2018); Dewi et al (2017); Dewi et al (2020); Rahmayanti et al (2021) The effect of perceived ease of use (X2) on repurchases intentions (Y) is 0.343; perceived ease of use has a positive and significant effects on repurchases intentions. This means that the higher the level of customers' perceived ease of use , the higher chance that repurchases intentions will occur.…”
Section: Methodsmentioning
confidence: 71%
“…This means that the higher the level of customers' perceived ease of use , the higher chance that repurchases intentions will occur. The result supported by Yasa et al (2014); Wida et al (2016); Puspitasari & Briliana (2018); Subagio et al (2018); Keni (2020); Rahmayanti et al (2021);Miandari et al (2021) Effect of perceived usefulness (X1) on trust (M) is 0.318; perceived usefulness has a positive significant effects on consumers' trust. Higher the level of consumers' perceived usefulness, the level of consumers' trust will increase.…”
Section: Methodsmentioning
confidence: 78%
“…Modification of the TAM theory by using additional variables has been carried out in various studies such as those conducted by Hanafizadeh et al (2014), in the context of e-wallet with the addition of trust and pleasure variables, Nelwan et al (2021), with the trust variable in his research on mobile banking and internet banking, in the context of mobile banking Alalwan et al (2018), added the variables of pleasure, innovation and trust, and Akbari et al (2020), in the context of acceptance of 5G technology by using trust as a mediating variable between perceived ease of use and perceived usefulness on intention to use. Empirical results from previous studies (Madhavaiah & Bashir, 2015;Alalwan et al, 2017;Alalwan et al, 2018;Giovanis et al, 2019;Dewi et al, 2020;Miandari et al, 2021;Rahmayanti et al, 2021;Nelwan et al, 2021;Nonis, 2022), which uses the TAM theory with variables of perceived ease of use, perceived usefulness, belief and behavioral intentions showing varying results, or there are differences. -differences in perception that affect consumer or customer intentions towards the use of new technology.…”
Section: Introductionmentioning
confidence: 98%
“…The more it provides high benefits to electronic money users, the higher the interest of users to use their electronic money services in the future. Previous research conducted by Ertemel and Civelek, 2020;Siti and Totok, 2022;Rahmayanti et al, 2021) showed that perceived usefulness had a positive and significant effect on decision to use.…”
Section: The Influence Of Perceived Usefulness On Decision To Usementioning
confidence: 87%
“…If a system is relatively easy to use, users will be more willing to learn more about its features and ultimately intend to continue using it. Previous research conducted by (Putri and Iriani, 2020;Lestary et al, 2020;Tik, 2018;Rahmayanti et al, 2021) showed that perceived ease of use had a positive and significant effect on decision to use.…”
Section: The Influence Of Perceived Ease Of Use On Decision To Usementioning
confidence: 90%